2008
DOI: 10.1038/bmt.2008.314
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following unrelated cord blood transplant in 136 patients with malignant and non-malignant diseases: a report from the Australian and New Zealand children's haematology and oncology group

Abstract: Unrelated umbilical cord blood (UCB) is an alternative stem cell source for paediatric patients lacking a matched related or unrelated marrow donor. We report the results of all paediatric unrelated UCB transplants performed in Australia and New Zealand over a 10-year period. A total of 135 patients were transplanted, 100 for malignant disease (74%) and 35 for non-malignant disorders. The majority (88%) of patients received an HLA-mismatched graft. The median infused total nucleated cell dose was 4.7 Â 10 7 /k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
5
10
2
Order By: Relevance
“…Disease-free survival was best for those patients who received a 6/6 matched cord blood (60% vs 38%) and comparable for those patients who received 8/ 8 matched unrelated bone marrow or 4/6 or 5/6 matched cord blood units. The Australian and New Zealand groups recently reported a 5 year survival of 41% for 100 children with malignant diseases and a 65% 5 year survival for 36 children with non-malignant diseases [14]. Similar results have been reported by the American COBLT study [15].…”
Section: Unrelated Cord Blood Transplantssupporting
confidence: 58%
“…Disease-free survival was best for those patients who received a 6/6 matched cord blood (60% vs 38%) and comparable for those patients who received 8/ 8 matched unrelated bone marrow or 4/6 or 5/6 matched cord blood units. The Australian and New Zealand groups recently reported a 5 year survival of 41% for 100 children with malignant diseases and a 65% 5 year survival for 36 children with non-malignant diseases [14]. Similar results have been reported by the American COBLT study [15].…”
Section: Unrelated Cord Blood Transplantssupporting
confidence: 58%
“…Although a trend towards improved neutrophil engraftment with a CD34+ cell dose greater than 1.7 × 10 5 was seen, this did not reach statistical significance (data not shown). The significance of cell dose on overall survival seen in this cohort was not observed in a recent review of 136 Australian paediatric patients who received a cord blood transplant 21 . In this study CD34+ cell dose was predictive of neutrophil engraftment but not of overall survival.…”
Section: Discussioncontrasting
confidence: 72%
“…The significance of cell dose on overall survival seen in this cohort was not observed in a recent review of 136 Australian paediatric patients who received a cord blood transplant. 21 In this study CD34+ cell dose was predictive of neutrophil engraftment but not of overall survival. This discrepancy may be explained by the inclusion of adults in our cohort who had lower median TNC and CD34+ cell doses and likely contributed to the effects of the survival difference seen at lower transplanted cell doses.…”
Section: Discussionmentioning
confidence: 56%
“…In another recent study of children with leukemia and myelodysplastic syndrome (MDS), Shaw et al [9] reported a cumulative 3-year incidence of TRM after MAC allo-HSCT was 10% for MSD graft recipients, compared with 27% for matched unrelated donor (MUD) graft recipients. TRM in children after MAC and umbilical cord blood (UBC) transplantation (UCBT) is significantly higher, ranging from 20% to 52% [6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%